Gaya Kepemimpinan dan Supervisi Kepala Madrasah dalam Meningkatkan Profesionalitas Guru di MA Putra Al-Ishlahuddiny Kediri - Muhammad Amir Mahmud (MANAZHIM, 2023)
The role of the Madrasa Head as a central figure in the educational environment is very important in an institution, so that the leadership and supervision style of the Madrasah Head makes a positive contribution to the professionalism teachers of Madrasah Aliyah Putra al-Ishlahuddiny Kediri West Lombok. The aims of this study are 1) To determine the leadership style of the Head of Madrasah Aliyah Putra Al-Ishlahuddiny Kediri, West Lombok. 2) To find out the Madrasah Head’s implementation of the supervision at Madrasah Aliyah Putra Al-Ishlahuddiny Kediri West Lombok. 3) To find out the Madrasah Head’s contribution of the leadership style and supervision in increasing the professionalism teachers of Madrasah Aliyah Putra Al-Ishlahuddiny Kediri West Lombok. This research is a qualitative research, while the data obtained in this study were the head of the Madrasah, the teachers, and several students of Madrasah Aliyah Putra Al-Ishlahuddiny Kediri, West Lombok. Data collection techniques used are interviews, documentation and observation. The conclusions of this thesis research are 1) The leadership style of the Principal of Madrasah Aliyah Putra al-Ishlahuddiny Kediri in improving teacher professionalism uses a democratic leadership style which means that they are happy to receive suggestions, ideas and criticism from subordinates, communicate policies and problems, build work teams as a family. 2) The supervision carried out by the Madrasah Head in improving teacher professionalism is in a Collaborative form, and 3) The leadership and supervision style of the Madrasah Head makes a significant contribution in increasing the professionalism teachers of Madrasah Aliyah Putra Al-Ishlahuddiny Kediri West Lombok. Based on the conclusions of the research, the Head of Madrasah should make an effort and be committed to developing personal performance (especially teachers) towards the expected professionalism, to create all of this, Madrasah leaders must pay attention to Collaborative Democracy Leadership Style (Collaborative Democracy).